2020
DOI: 10.1002/ece3.6615
|View full text |Cite
|
Sign up to set email alerts
|

“Into and Out of” the Qinghai‐Tibet Plateau and the Himalayas: Centers of origin and diversification across five clades of Eurasian montane and alpine passerine birds

Abstract: Encompassing some of the major hotspots of biodiversity on Earth, large mountain systems have long held the attention of evolutionary biologists. The region of the Qinghai‐Tibet Plateau (QTP) is considered a biogeographic source for multiple colonization events into adjacent areas including the northern Palearctic. The faunal exchange between the QTP and adjacent regions could thus represent a one‐way street (“out of” the QTP). However, immigration into the QTP region has so far received only little attention,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 111 publications
3
38
3
Order By: Relevance
“…Ancestral Trait Reconstruction of Elevation and Body Mass. We performed an ancestral trait reconstruction using a well-established phylogeny of Passeridae (24), which includes all 27 species from seven genera: Montifringilla, Onychostruthus, Pyrgilauda, Petronia, Gymnoris, Passer, and Hypocryptadius. We collected the elevation records from eBird (https://ebird.org/) and China Bird Reports (http://www.birdreport.cn).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancestral Trait Reconstruction of Elevation and Body Mass. We performed an ancestral trait reconstruction using a well-established phylogeny of Passeridae (24), which includes all 27 species from seven genera: Montifringilla, Onychostruthus, Pyrgilauda, Petronia, Gymnoris, Passer, and Hypocryptadius. We collected the elevation records from eBird (https://ebird.org/) and China Bird Reports (http://www.birdreport.cn).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to most of their closest relatives among the Old World Sparrows (Passeridae), the snowfinches have a larger body size, darker plumage, and increased metabolic rate ( 20 , 21 ). Previous studies suggested that snowfinches, consisting of the three genera of Montifringilla , Onychostruthus , and Pyrgilauda , form a monophyletic group ( 22 24 ). It is therefore possible that the observed similarities in phenotypic adaptations to high elevation are inherited from their common ancestor, assuming that the ancestral species had already adapted to this high-elevation environment.…”
mentioning
confidence: 99%
“…To estimate the spatio‐temporal origins of species endemic to the TP, we compiled the ancestral ranges and age estimates of dispersal events of TP species based on the DEC models. Although the dispersal events might have involved both ‘into TP’ dispersals and ‘out of TP’ dispersals (Deng et al., 2020; Päckert et al., 2020), we only considered the ‘into TP’ dispersal events that represented the first establishment of a specific clade on the TP. Given that all of the terrestrial organisms here should have originated outside the TP, the ‘into TP’ dispersal events could be expected to have occurred earlier than the ‘out of TP’ dispersal events.…”
Section: Methodsmentioning
confidence: 99%
“…55–50 million years ago (Ma) due to the Indo–Asian collision (Hu, Garzanti, et al., 2016; Royden et al., 2008). As such, species endemic to the TP are expected to have colonized from surrounding regions followed by vicariant speciation and diversification (Päckert et al., 2020; Wen et al., 2014). However, given that strong reconfiguration of the geographical setting and atmospheric circulation have profoundly altered the biota on the TP over the past 50 Myr (He et al., 2020; Mosbrugger et al., 2018), the origins of these species and their time of arrival on the TP remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation